First detection of Nosema ceranae in honey bees (Apis mellifera L.) of the Macaronesian archipelago of Madeira - Lopes, Ana (2023)
The Microsporidia Nosema ceranae is an invasive pathogen affecting honey bee health, particularly in warm climates. In this study, N. ceranae was detected for the first time in honey bees (Apis mellifera L.) of the Madeira archipelago, indicating that this pathogen is now spreading across the entire Macaronesia. Nosema apis was not detected, and the high prevalence (67.7%) of N. ceranae indicates its dominance over N. apis.